PERANCANGAN SISTEM INFORMASI MANAJEMEN SUMBER DAYA MANUSIA (HRIS) YANG TERINTEGRASI BERBASIS WEB - Bias Yulisa Geni; Iqbal Febrianwar; Henri Septanto (Yayasan Pendidikan Cahaya Budaya Indonesia, 2026)
This study emerges as a solution to the administrative challenges at Hotel Pinangsia, which still relies on conventional systems for attendance, leave/permit administration, and payroll calculations, resulting in delays in recap, inconsistent information, and obstacles in preparing executive reports. The objective of this research is to design and implement a web-based Human Resource Information System (HRIS) as an integrated data reference that consolidates essential operational modules. The methodology employed includes qualitative strategies (field observations and in-depth discussions) to identify requirement specifications, software construction using the Agile Scrum paradigm with an iterative approach, and functionality verification through black-box testing and user acceptance testing (UAT). The developed platform integrates multi-layered OTP authentication, an attendance system utilizing face recognition (verifying face–location–time), a leave/permit submission and approval mechanism, payroll administration with periodic payslips, as well as comprehensive employee and user database management. Testing results confirm that all fundamental scenarios operate according to acceptance criteria, accelerating payroll recap processes, enhancing the credibility of attendance data, and streamlining approval coordination. The practical impact is the optimization of operational efficiency and transparency in decision-making processes; future development agendas include comprehensive non-functional evaluation (load testing, security assessment, reliability testing), expansion of audit trails, development of mobile/PWA access channels with geo-fencing, and the implementation of KPI-based managerial analytics dashboards.